An examination of older men's body image: How men 65 years and older perceive, experience, and cope with their aging bodies. (September 2020) - Bennett, Erica V.; Hurd, Laura C.; Pritchard, Elizabeth M.; Colton, Tayler; Crocker, Peter R.E.
Highlights: We examined how men aged 65–83 coped with age-related body changes. Men were concerned with yet concurrently grateful for their aging bodies. Participants stressed the need to accept age-related body changes. Men engaged in social comparisons to others and to their younger selves. Men were concerned with and regulated weight using diet monitoring and exercise. Abstract: We examined how older men perceived, experienced, and coped with age-related changes to their appearance, body function, and health. Data from semi-structured interviews with 28 men aged 65–83 living in a large urban Canadian city and diverse in ethnocultural background (European, East Asian, and South Asian) and sexual orientation (heterosexual and gay) were analyzed through a reflexive thematic analysis. Four overarching themes were constructed from the participants' accounts. Participants were ambivalent about their aging bodies; they were concerned about certain changes to their bodies, yet concurrently grateful for their retained health and body function. The men stressed the need to accept age-related body changes through pragmatism, awareness of challenging body-related cognitions and emotions without overidentification or suppression, and adjustments to expectations and activities. Participants engaged in upward and downward social comparisons to assess their aging bodies in relation to others and to their younger selves. Weight concerns were prominent. The men worried about their weight, with particular attention to their stomach, and were physically active and ate a healthy diet to manage their weight. This study contributes to body image theorizing by including older diverse men and can inform interventions aiming to enhance men's later life psychological adjustment.